Predictors of Graft Failure in Young Active Patients Undergoing Hamstring Autograft Anterior Cruciate Ligament Reconstruction With or Without a Lateral Extra-articular Tenodesis: The Stability Experience. Issue 2 (February 2022) - Firth, Andrew D.; Bryant, Dianne M.; Litchfield, Robert; McCormack, Robert G.; Heard, Mark; MacDonald, Peter B.; Spalding, Tim; Verdonk, Peter C.M.; Peterson, Devin; Bardana, Davide; Rezansoff, Alex; ,; et al.
Background: Anterior cruciate ligament (ACL) reconstruction (ACLR) has higher failure rates in young active patients returning to sports as compared with older, less active individuals. Augmentation of ACLR with an anterolateral procedure has been shown to reduce failure rates; however, indications for this procedure have yet to be clearly defined. Purpose/Hypothesis: The purpose of this study was to identify predictors of ACL graft failure in high-risk patients and determine key indications for when hamstring ACLR should be augmented by a lateral extra-articular tenodesis (LET). We hypothesized that different preoperative characteristics and surgical variables may be associated with graft failure characterized by asymmetric pivot shift and graft rupture. Study Design: Case-control study; Level of evidence, 3. Methods: Data were obtained from the Stability 1 Study, a multicenter randomized controlled trial of young active patients undergoing autologous hamstring ACLR with or without a LET. We performed 2 multivariable logistic regression analyses, with asymmetric pivot shift and graft rupture as the dependent variables. The following were included as predictors: LET, age, sex, graft diameter, tear chronicity, preoperative high-grade knee laxity, preoperative hyperextension on the contralateral side, medial meniscal repair/excision, lateral meniscal repair/excision, posterior tibial slope angle, and return-to-sports exposure time and level. Results: Of the 618 patients in the Stability 1 Study, 568 with a mean age of 18.8 years (292 female; 51.4%) were included in this analysis. Asymmetric pivot shift occurred in 152 (26.8%) and graft rupture in 43 (7.6%). The addition of a LET (odds ratio [OR], 0.56; 95% CI, 0.37-0.83) and increased graft diameter (OR, 0.62; 95% CI, 0.44-0.87) were significantly associated with lower odds of asymmetric pivot shift. The addition of a LET (OR, 0.40; 95% CI, 0.18-0.91) and older age (OR, 0.83; 95% CI, 0.72-0.96) significantly reduced the odds of graft rupture, while greater tibial slope (OR, 1.15; 95% CI, 1.01-1.32), preoperative high-grade knee laxity (OR, 3.27; 95% CI, 1.45-7.41), and greater exposure time to sport (ie, earlier return to sport) (OR, 1.18; 95% CI, 1.08-1.29) were significantly associated with greater odds of rupture. Conclusion: The addition of a LET and larger graft diameter were significantly associated with reduced odds of asymmetric pivot shift. Adding a LET was protective of graft rupture, while younger age, greater posterior tibial slope, high-grade knee laxity, and earlier return to sport were associated with increased odds of graft rupture. Orthopaedic surgeons should consider supplementing hamstring autograft ACLR with a LET in young active patients with morphological characteristics that make them at high risk of reinjury.